Exploring the Role of Meditation and Dispositional Mindfulness on Social Cognition Domains: A Controlled Study - Campos, Daniel; Modrego-Alarcón, Marta; López-del-Hoyo, Yolanda; González-Panzano, Manuel; Van Gordon, William; Shonin, Edo; Navarro-Gil, Mayte; García-Campayo, Javier (Frontiers in Psychology, 2019)
Research suggests that mindfulness can induce changes in the social domain, such as enhancing emotional connection to others, prosocial behavior, and empathy. However, despite growing interest in mindfulness in social psychology, very little is known about the effects of mindfulness on social cognition. Consequently, the aim of this study was to explore the relationship between mindfulness and social cognition by comparing meditators with nonmeditators on several social cognition measures. A total of 60 participants (meditators, n = 30; nonmeditators, n = 30) were matched on sex, age, and ethnic group, and then asked to complete the following assessment measures: Mindful Awareness Attention Scale (MAAS), Five Facet Mindfulness Questionnaire Short Form (FFMQ-SF), Interpersonal Reactivity Index (IRI), Revised Eyes Test, Hinting Task, Ambiguous Intentions and Hostility Questionnaire (AIHQ), Hospital Anxiety and Depression Scale (HADS), and Screening for Cognitive Impairment in Psychiatry (SCIP). The results showed that meditators reported higher empathy (except for the personal distress subscale), higher emotional recognition, higher Theory of Mind (ToM), and lower hostile attributional style/bias. The findings also demonstrated that dispositional mindfulness (both total score assessed with MAAS and mindfulness facets using the FFMQ) was associated with social cognition, although it was not equally correlated with all social cognition outcomes, and correlation patterns differ when analyses were conducted separately for meditators and nonmeditators. In addition, results showed potential predictors for each social cognition variable, highlighting nonreactivity to inner experience as a key component of mindfulness in order to explain social cognition performance. In summary, the findings indicated that the meditator sample performed better on certain qualities (i.e., empathy, emotional recognition, theory of mind, hostile attributional style/bias) in comparison to nonmeditators and, furthermore, support the notion that mindfulness is related to social cognition, which may have implications for the design of mindfulness-based approaches for use in clinical and nonclinical settings.